PuzzleArt Therapy: Connecting the Pieces in Search of Answers - Jennifer Fortuna (Scholarworks @ WMU, 2016)
Alli Berman, a New York based artist, provided the cover art for the Fall 2016 issue of The Open Journal of Occupational Therapy (OJOT). "Sunlight Underwater" is a 12 piece PuzzleArt painting made from acrylic on American maple that measures 22x30. The PuzzleArt concept began as a simple exercise that evolved into a therapeutic modality. When a sudden stroke impacted Berman's well-being and quality of life, it was art that helped her to make connections during recovery.